Fournier’s gangrene of the scrotum after inguinal hernia repair: case report - Vagholkar, Ketan; Kunal Deshmukh; Haragovind Sai; Tanay Purandare (International Surgery Journal, 2023)
Fournier’s gangrene is a severe necrotizing fasciitis affecting the scrotum, perianal and perineal region. Development of this condition after inguinal hernia repair is extremely rare. A 54-year-old diabetic male patient who had undergone right inguinal hernia repair in a private clinic presented with severe necrotizing infection of the scrotum, predominantly of the right side. He was referred to our surgical unit. Initial resuscitation followed by broad spectrum antibiotic therapy and aggressive debridement of necrotic tissue followed by closure of scrotum was performed with excellent outcome. The purpose of presenting this case is to create awareness about this complication after hernia repair surgery especially in cases with comorbidities like diabetes mellitus.